2016
DOI: 10.4236/jss.2016.42001
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Study of Parents’ Perceptions of Preschool Teaching Competencies in China

Abstract: Parents play an important role in children's education. Parents' expectations and evaluation of kindergarten teachers could foster the collaboration between kindergarten teachers and parents. However, parents' voice has largely been ignored in empirical research. The purpose of the present study is to reveal 3-6 years old children's parents' perceptions about 1) the importance of new kindergarten teacher standards and 2) their perceptions about kindergarten teachers' mastery of these standards. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…It was observed that parents in both groups had similar expectations from preschool teachers, such as preparing their children for primary school, ensuring children's socialization, and having positive affective characteristics for children. In the study conducted by Cui et al (2016), it is seen that parents expressed their views on the dimensions of love, respect, patience, and preparation for primary school. Research supports these expectations and suggests that developing a sense of trust in refugee children is very important for inclusive education.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that parents in both groups had similar expectations from preschool teachers, such as preparing their children for primary school, ensuring children's socialization, and having positive affective characteristics for children. In the study conducted by Cui et al (2016), it is seen that parents expressed their views on the dimensions of love, respect, patience, and preparation for primary school. Research supports these expectations and suggests that developing a sense of trust in refugee children is very important for inclusive education.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…It is seen that the studies conducted so far are related to recommendations to teachers, teachers' perceptions and attitudes, policies, family participation, administrators' opinions, the experiences of Syrian children in preschool classrooms and studies to understand the peer culture they create, problems and interventions (Özger & Akanser, 2019;Şayan, 2022;Tuncer, 2020). When the relevant literature is examined, there are studies on parents' expectations from preschool teachers and educational institutions (Çetinkaya et al, 2021;Cui et al, 2016;Konca, 2020). However, there is no comparative study on the expectations of families from different cultures whose children receive preschool education from teachers in the context of inclusive education.…”
Section: Introductionmentioning
confidence: 99%
“…When it comes to the personality traits preschool teachers must have, mothers emotionally expect them to be kind-hearted, cheerful and tolerant whereas fathers expect them -far from being emotional -to be aware of their responsibilities and open to improvement so that they can be seen as a role model for their children. Cui, Valcke and Vanderlinde (2016) stated in their study that parents defined the most important competencies of preschool teachers as "respect" and "love". Most of the parents defined the professional skills that preschool teachers must have as "creating different learning environments".…”
Section: Discussionmentioning
confidence: 99%
“…People may have different expectations for kindergarten teachers and teachers working in the formal education system. According to Cui et al (2016), Chinese parents' expectations for a good kindergarten teacher are likely to be related to "love" and "respect" to children. These are also competencies of teachers listed in "Ministry of Education (2012).…”
Section: Subtheme: Important Emotional Supportmentioning
confidence: 99%
“…None of the qualities reported was relevant to children's emotional needs (Liu and Meng, 2009). Social expectations of a good teacher in kindergarten in China are found to be related to children's social and emotional needs, such as love and respect for children (Cui et al, 2016). This may indicate that Chinese kindergarten teachers would be more aware of providing emotional support for the children than the teachers working in the formal education system.…”
mentioning
confidence: 95%